2016
DOI: 10.20944/preprints201607.0062.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonlinear growth effect of remittances in recipient countries: an econometric analysis of remittances-growth nexus in Bangladesh

Abstract: Abstract:The paper examines the impact of inward remittances flows on per capita GDP growth in Bangladesh during 1976-2012. We find that the growth effect of remittances is negative at first but becomes positive at a later stage, an evidence of a non-linear relationship. Unproductive use of remittances was rampant in the beginning when they were received by migrant families but better social and economic investments led to more productive utilisation of remittances receipts at later periods. This was the possi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Note that the impact of remittances on economic growth could be nonlinear (Chami et al, , ; Abdih et al, ; Hassan et al, ). On the one hand, Chami et al ( and 2009) show that a high level of remittances to GDP ratio tends to have a negative impact on the labor supply of remittance‐dependent households, which eventually retards economic growth.…”
Section: Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the impact of remittances on economic growth could be nonlinear (Chami et al, , ; Abdih et al, ; Hassan et al, ). On the one hand, Chami et al ( and 2009) show that a high level of remittances to GDP ratio tends to have a negative impact on the labor supply of remittance‐dependent households, which eventually retards economic growth.…”
Section: Empirical Modelmentioning
confidence: 99%
“…Abdih et al () also argue that a country with a high level of remittance inflows over a long period tends to feel less need for reforms, leaving the country with a narrow base prone to exogenous shocks. On the other hand, Hassan et al () posit a nonlinear relationship between remittances and growth and show that the effect of remittances is negative at first, before becoming positive at a later stage. This implies that remittances are used unproductively at a low level, followed by more productive subsequent utilization.…”
Section: Empirical Modelmentioning
confidence: 99%
“…Siddidui (2004) classified the different types of agents and institutions involved in remittances' transfer process in Bangladesh including commercial banks. The study of Hassan et al (2012) also suggested that positive effect of remittances on the growth rate of the economy is channeled through its interaction with the financial sector of Bangladesh. Orozco and Fedewa (2005) attempted to explain the way by which remittances can influence the financial sector.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For instance, using a sample of 70 countries, Chami, Hakura, and Montiel () found that the effect of remittance inflows on growth volatility is highly nonlinear with the stabilizing effects of remittance inflows being greater when remittances are below 2% of GDP. Meanwhile, Hassan, Shakur, and Bhuyan () found a nonlinear relationship between remittances and growth in Bangladesh: they reported that the growth effect of remittances is negative at first but becomes positive at a later stage. Taking into consideration the common belief that both output volatility and economic growth impact on unemployment, it becomes quite plausible to assume that the nonlinear effects of remittances would spill over to unemployment.…”
Section: Introductionmentioning
confidence: 99%